Global, regional, and national prevalence, disability adjusted life years, and time trends for refraction disorders, 1990-2019: findings from the global burden of disease study 2019 - He-Yan Li; Yue-Ming Liu; Li Dong; Rui-Heng Zhang; Wen-Da Zhou; Hao-Tian Wu; Yi-Fan Li; Ya-Xing Wang; Wen-Bin Wei (BMC, 2021)
Abstract Background To evaluate global burden of refraction disorders by year, age, region, gender, socioeconomic status and other national characteristics in terms of disability adjusted life years (DALYs) and prevalence from Global Burden of Disease (GBD) study 2019 and World Bank Open Data 2019. Methods Global, regional, and national DALY numbers, crude DALY rates, age-standardized DALY and prevalence rates of refraction disorders were acquired from the GBD study 2019. Mobile cellular subscriptions, urban population, GDP per capita, access to electricity and total fertility rate were obtained from the World Bank to explore the factors that influenced the health burden of refraction disorders. Kruskal-Wallis test, linear regression and multiple linear regression were performed to evaluate the associations between the health burden with socioeconomic levels and other national characteristics. Wilcoxon Signed-Rank Test was used to investigate the gender disparity. Results Globally, age-standardized DALY rates of refraction disorders decreased from 88.9 (95% UI: 60.5-120.3) in 1990 to 81.5 (95% UI: 55.0-114.8) in 2019, and might fall to 73.16 (95% UI: 67.81-78.51) by 2050. Age-standardized prevalence rates would also reduce to 1830 (95% UI: 1700-1960) by 2050, from 2080 (95% UI: 1870-2310) in 1990 to 1960 (95% UI: 1750-2180) in 2019. In low SDI region, age-standardized DALY rates (equation: Y = 114.05*X + 27.88) and prevalence rates (equation: Y = 3171.1*X + 403.2) were positively correlated with SDI in linear regression respectively. East Asia had the highest blindness rate caused by refraction disorders in terms of age-standardized DALY rates (11.20, 95% UI: 7.38-16.36). Gender inequality was found among different age groups and SDI regions. Conclusion Health burden of refraction disorders decreased in recent years, and may continue to alleviate in the next three decades. Older ages, females and lower socioeconomic status were associated with higher refraction disorders health burden.